Exploring The Link Between Demographic Factors and Non-Suicidal Self-Injury (NSSI) Among Indonesian Adolescents : An Educational Psychology Perspective - Wiswanti, Inge Uli; Hendrawan, Donny (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to explore the relationship between demographic factors and self-injury behavior (Non-Suicidal Self-Injury/ NSSI) in Indonesian adolescents from an educational psychology perspective. Using a cross-sectional study method with a quantitative approach, this study involved 213 adolescents aged 12-18 years (Mage = 14.95; SD = 1.52). Participants were recruited via a purposive sampling method. The Deliberate Self-Harm Inventory (DSHI) was employed to assess self-injurious behaviors. Inferential analysis utilized the Chi-square test to examine associations between categorical demographic variables, while one-way ANOVA was conducted to identify significant differences in mean NSSI scores across independent groups. The result showed that the proportion of participants who reported doing NSSI did not differ by socioeconomic status and education level. However, a significant association was found between NSSI and gender. Furthermore, it was also found a significant difference in the degree of NSSI between male and female adolescents. Females were more potential than males to do NSSI. These findings emphasize the imperative for educational psychology policies to incorporate routine screenings, targeted intervention or educational programs to alleviate NSSI among female adolescents. It should also implement professional training and culturally sensitive mental health services to create stigma-free environments that promote early intervention and resilience-building.